Evaluation of Online Learning at Public Junior High School 2 Gorontalo - Nuzlan Botutihe; Widya Kurniati Mohi (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This study aims to obtain on overview of online learning at SMP Negeri 2 Gorontalo. The research method uses a qualitative research type with a descriptive approach. Data collection techniques were carried out through interviews with a number of informations and observations and recording of secondary data related to research problems. The results of the study conclude that the evaluation of online learning at SMP Negeri 2 Gorontalo is based on evaluation indicators, namely the traditional approach and the system approach, namely online learning at SMP Neger 2 Gorontalo has not been effectifely demonstated by the participation of students in learning. Who are lacking in learning discipline. Human resources in this case educator or teachers lack expertise where, the quality of the material provided by the teacher or educator is still less attractive and varied. the availability of discussion or interaction time between educator and teachers. The number of students decreases so that it affects the lack of creativity and innovation of students in learning, and students are less ready to face assignments and exams from scholl which affect the decline in achievement and quality than students.